Estimation of the Rate of Unrecognized Cross-Contamination with Mycobacterium tuberculosis in London Microbiology Laboratories - Ruddy, M. (American Society for Microbiology, 2002)
Isolates from patients with confirmed tuberculosis from London were collected over 2.5 years between 1995 and 1997. Restriction fragment length polymorphism (RFLP) analysis was performed by the international standard technique as part of a multicenter epidemiological study. A total of 2,779 samples representing 2,500 individual patients from 56 laboratories were examined. Analysis of these samples revealed a laboratory cross-contamination rate of between 0.54%, when only presumed cases of cross-contamination were considered, and 0.93%, when presumed and possible cases were counted. Previous studies suggest an extremely wide range of laboratory cross-contamination rates of between 0.1 and 65%. These data indicate that laboratory cross-contamination has not been a common problem in routine practice in the London area, but in several incidents patients did receive full courses of therapy that were probably unnecessary.